Using linear function concepts, it is found that the slopes and intercepts of the functions are given as follows:
a) -4.
b) P = 25.
c) 2.
d) P = 5.
<h3>What is a linear function?</h3>
A linear function is modeled by:
y = mx + b
In which:
- m is the slope, which is the rate of change, that is, by how much y changes when x changes by 1.
- b is the y-intercept, which is the value of y when x = 0, and can also be interpreted as the initial value of the function.
The demand is given by:
D = 100 - 4P.
Hence the slope is of -4. The demand is equals to zero when:
100 - 4P = 0 -> P = 25.
The supply is given by:
QS = -10 + 2P.
Hence the slope is of 2. The supply is equals to zero when:
-10 + 2P = 0 -> P = 5.
More can be learned about linear function concepts at brainly.com/question/24808124
#SPJ1
50 maybe
Step-by-step explanation:
because 200 lollipops 4 in each bag
And 150 pencils 3 in each bag
(i dont think this is right)
For
, on the left we have
, and on the right,
![\dfrac{\sin2\theta}{2\sin\theta}=\dfrac{2\sin\theta\cos\theta}{2\sin\theta}=\cos\theta](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csin2%5Ctheta%7D%7B2%5Csin%5Ctheta%7D%3D%5Cdfrac%7B2%5Csin%5Ctheta%5Ccos%5Ctheta%7D%7B2%5Csin%5Ctheta%7D%3D%5Ccos%5Ctheta)
(where we use the double angle identity:
)
Suppose the relation holds for
:
![\displaystyle\sum_{n=1}^k\cos(2n-1)\theta=\dfrac{\sin2k\theta}{2\sin\theta}](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%3D1%7D%5Ek%5Ccos%282n-1%29%5Ctheta%3D%5Cdfrac%7B%5Csin2k%5Ctheta%7D%7B2%5Csin%5Ctheta%7D)
Then for
, the left side is
![\displaystyle\sum_{n=1}^{k+1}\cos(2n-1)\theta=\sum_{n=1}^k\cos(2n-1)\theta+\cos(2k+1)\theta=\dfrac{\sin2k\theta}{2\sin\theta}+\cos(2k+1)\theta](https://tex.z-dn.net/?f=%5Cdisplaystyle%5Csum_%7Bn%3D1%7D%5E%7Bk%2B1%7D%5Ccos%282n-1%29%5Ctheta%3D%5Csum_%7Bn%3D1%7D%5Ek%5Ccos%282n-1%29%5Ctheta%2B%5Ccos%282k%2B1%29%5Ctheta%3D%5Cdfrac%7B%5Csin2k%5Ctheta%7D%7B2%5Csin%5Ctheta%7D%2B%5Ccos%282k%2B1%29%5Ctheta)
So we want to show that
![\dfrac{\sin2k\theta}{2\sin\theta}+\cos(2k+1)\theta=\dfrac{\sin(2k+2)\theta}{2\sin\theta}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csin2k%5Ctheta%7D%7B2%5Csin%5Ctheta%7D%2B%5Ccos%282k%2B1%29%5Ctheta%3D%5Cdfrac%7B%5Csin%282k%2B2%29%5Ctheta%7D%7B2%5Csin%5Ctheta%7D)
On the left side, we can combine the fractions:
![\dfrac{\sin2k\theta+2\sin\theta\cos(2k+1)\theta}{2\sin\theta}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csin2k%5Ctheta%2B2%5Csin%5Ctheta%5Ccos%282k%2B1%29%5Ctheta%7D%7B2%5Csin%5Ctheta%7D)
Recall that
![\cos(x+y)=\cos x\cos y-\sin x\sin y](https://tex.z-dn.net/?f=%5Ccos%28x%2By%29%3D%5Ccos%20x%5Ccos%20y-%5Csin%20x%5Csin%20y)
so that we can write
![\dfrac{\sin2k\theta+2\sin\theta(\cos2k\theta\cos\theta-\sin2k\theta\sin\theta)}{2\sin\theta}](https://tex.z-dn.net/?f=%5Cdfrac%7B%5Csin2k%5Ctheta%2B2%5Csin%5Ctheta%28%5Ccos2k%5Ctheta%5Ccos%5Ctheta-%5Csin2k%5Ctheta%5Csin%5Ctheta%29%7D%7B2%5Csin%5Ctheta%7D)
![=\dfrac{\sin2k\theta+\sin2\theta\cos2k\theta-2\sin2k\theta\sin^2\theta}{2\sin\theta}](https://tex.z-dn.net/?f=%3D%5Cdfrac%7B%5Csin2k%5Ctheta%2B%5Csin2%5Ctheta%5Ccos2k%5Ctheta-2%5Csin2k%5Ctheta%5Csin%5E2%5Ctheta%7D%7B2%5Csin%5Ctheta%7D)
![=\dfrac{\sin2k\theta(1-2\sin^2\theta)+\sin2\theta\cos2k\theta}{2\sin\theta}](https://tex.z-dn.net/?f=%3D%5Cdfrac%7B%5Csin2k%5Ctheta%281-2%5Csin%5E2%5Ctheta%29%2B%5Csin2%5Ctheta%5Ccos2k%5Ctheta%7D%7B2%5Csin%5Ctheta%7D)
![=\dfrac{\sin2k\theta\cos2\theta+\sin2\theta\cos2k\theta}{2\sin\theta}](https://tex.z-dn.net/?f=%3D%5Cdfrac%7B%5Csin2k%5Ctheta%5Ccos2%5Ctheta%2B%5Csin2%5Ctheta%5Ccos2k%5Ctheta%7D%7B2%5Csin%5Ctheta%7D)
(another double angle identity:
)
Then recall that
![\sin(x+y)=\sin x\cos y+\sin y\cos x](https://tex.z-dn.net/?f=%5Csin%28x%2By%29%3D%5Csin%20x%5Ccos%20y%2B%5Csin%20y%5Ccos%20x)
which lets us consolidate the numerator to get what we wanted:
![=\dfrac{\sin(2k+2)\theta}{2\sin\theta}](https://tex.z-dn.net/?f=%3D%5Cdfrac%7B%5Csin%282k%2B2%29%5Ctheta%7D%7B2%5Csin%5Ctheta%7D)
and the identity is established.